Epidemiology of rubella and congenital rubella syndrome in Japan before 1989. Issue 16 (7th April 2016) - Ueda, Kohji
Abstract: Epidemiological studies of rubella and congenital rubella syndrome (CRS) in Japan have been conducted since the first nationwide rubella epidemic of 1965–1969 and subsequent epidemics of 1975–1977, 1982, 1987–1988, and 1992–1993. Rubella was non-endemic in Japan before the 1975–1977 epidemic, and endemic thereafter. Japan started a selective rubella vaccination program for junior high school girls in 1977, and universal rubella vaccination of children of both sexes in 1989. No nationwide rubella epidemics have occurred since 1994. Only three children with CRS were reported in Japan before 1964; however, many children with CRS were identified in 1965 when a rubella epidemic struck Okinawa, which has many the United States military bases. After the 1965–1969 and 1975–1977 rubella epidemics on the Japanese mainland, small numbers of children with CRS were identified (hospital survey). These findings led to the hypothesis that, compared to U.S. rubella virus strains, Japanese strains of rubella virus are less teratogenic. This hypothesis strongly affected the development of rubella vaccines in Japan. However, retrospective seroepidemiological studies attributed the CRS in many children in Okinawa to the high rate of rubella infection in pregnant women. According to the survey conducted at special schools for the deaf, 83, 232, 77, and 167 children were born with CRS on the Japanese mainland respectively after the 1965–1969, 1975–1977, 1982, and 1987–1988 nationwide rubella epidemics, suggesting that the incidence of CRS in Japan is in fact comparable to that in the U.S. and Europe. Rubella epidemics in children have been effectively prevented since 1994. However, a rubella outbreak among adult males and CRS occurred between 2012 and 2014.